Physicochemical and Agronomic Effects of Sago Waste-Derived Biochar and Compost on Seedling Survival Across Sago Accessions - Masluki Masluki; Mutmainnah Mutmainnah; Erni Firdamayanti; Sri Hastuty Saruman; Ulfah Zakiyah Hamdani (Agro Bali : Agricultural Journal, 2026)
Sago (Metroxylon sagu Rottb.) is an important tropical starch-producing palm with substantial potential to support food security and climate-resilient agriculture in Indonesia. However, sago-processing activities generate large quantities of lignocellulosic residues that are commonly discarded without proper utilization, thereby contributing to environmental pollution and biomass waste accumulation. This study evaluated the physicochemical characteristics of sago waste-derived biochar and compost and assessed their effectiveness as planting media amendments for improving sago seedling establishment during acclimatization. Biochar was produced through slow pyrolysis of sago bark residues at 300–500°C, whereas compost was prepared from sago pulp through controlled microbial fermentation. Chemical composition was analyzed using X-ray fluorescence (XRF), while microstructural characteristics and elemental composition were evaluated using scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM–EDX). XRF analysis revealed that sago pulp compost contained high silica concentrations (40.50%), whereas sago pith was enriched with potassium (25.63%) and calcium (27.07%). SEM observations revealed highly porous biochar structures with dominant carbon content ranging from 89.35% to 94.42%, indicating favorable properties for water retention and nutrient adsorption. Agronomic evaluation showed that the application of 300 g biochar + 300 g pith + 300 g compost significantly increased seedling survival to 96.43% at 12 weeks after application compared with the untreated control (P ≤ 0.05). To the best of our knowledge, this is the first study to integrate the physicochemical characterization of sago-processing residues (biochar and compost) with an accession-based agronomic evaluation of seedling survival, thereby linking waste valorization to nursery performance in M. sagu. The findings demonstrate that sago-processing residues can be converted into effective organic amendments and provide a mechanistic, evidence-based basis for circular biomass utilization in tropical nursery systems.